Muscle Activity and Kinematics During Three Hamstring Strengthening Exercises Compared to Sprinting: A Cross-Sectional Study. - Adelso Jorge; Eric Lichtenstein; Oliver Faude; Ralf Roth (North American Sports Medicine Institute, 2024)
# Background During sprinting, the biceps femoris long head predominantly gets injured, while hamstring strengthening exercises predominantly activate the semitendinosus more effectively. Understanding how joint dominance influences hamstring activity may offer clarity on appropriate exercise selection in strengthening programs. # Purpose This study compared three hip-dominant hamstring exercises: the rocker, perpetuum mobile fast and slow (PMfast and PMslow) and the Nordic Hamstring exercise (NHE) on their potential to simulate sprint-like activity and kinematics. # Methods Muscle activity of the posterior kinetic chain (biceps femoris, semitendinosus, gluteus maximus, and medial gastrocnemius) was measured with surface electromyography (sEMG) during the exercises and treadmill running at 75% of the individual maximal sprint velocity in male athletes. sEMG data were normalized to maximal sprinting. 3D-motion capture was employed to assess hip and knee angles. # Results Eight male athletes were included (age: 24.0 years ± SD 2.9; body mass: 76.8 kg ± 7.7; height: 1.79 m ± 0.08). Greater activity of the hamstrings occurred during the explosive exercises ranging from 63.9% [95%CI: 56.3-71.5%] (rocker) to 49.0% [95%CI: 40.4-57.6%] (PMfast) vs. 34.0% [95%CI: 29.1-38.9%] (NHE) to 32.1% [95%CI: 26.9-37.3%] (PMslow). The rocker showed greatest hamstring and gluteus maximus activity. Biceps femoris consistently showed greater activity than the semitendinosus across all exercises in peak (mean difference: 0.16, [95%CI: 0.07-0.26]) and average (mean difference: 0.06, [95%CI: 0.01-0.11]) activity. PMfast, PMslow and NHE demonstrated less hip flexion angle at peak hamstring activity than the rocker and high-speed running and every exercise showed less hamstring elongation stress than during high-speed running. # Discussion Hamstring activity is comparable to high-intensity treadmill running for NHE and PMslow, and greater for the rocker and PMfast. Gluteus maximus activity varied, with the rocker and PMfast showing greater activity than in sprinting. All examined exercises demonstrated their peak activity at short hamstring muscle length. # Level of evidence 3b